Time to diagnosis of Type I or II invasive epithelial ovarian cancers: a multicentre observational study using patient questionnaire and primary care records. (29th May 2015) - Lim, AWW; Mesher, D; Gentry‐Maharaj, A; Balogun, N; Widschwendter, M; Jacobs, I; Sasieni, P; Menon, U
Abstract : Objective: To compare time to diagnosis of the typically slow‐growing Type I (low‐grade serous, low‐grade endometrioid, mucinous, clear cell) and the more aggressive Type II (high‐grade serous, high‐grade endometrioid, undifferentiated, carcinosarcoma) invasive epithelial ovarian cancer (iEOC). Design: Multicentre observational study. Setting: Ten UK gynaecological oncology centres. Population: Women diagnosed with primary EOC between 2006 and 2008. Methods: Symptom data were collected before diagnosis using patient questionnaire and primary‐care records. We estimated patient interval (first symptom to presentation) using questionnaire data and diagnostic interval (presentation to diagnosis) using primary‐care records. We considered the impact of first symptom, referral and stage on intervals for Type I and Type II iEOC. Main outcome measures: Patient and diagnostic intervals. Results: In all, 78% of 60 Type I and 21% of 134 Type II iEOC were early‐stage. Intervals were comparable and independent of stage [e.g. median patient interval for Type I: early‐stage 0.3 months (interquartile range 0.3–3.0) versus late‐stage 0.3 months (interquartile range 0.3–4.5), P  = 0.8]. Twenty‐seven percent of women with Type I and Type II had diagnostic intervals of at least 9 months. First symptom (questionnaire) was also similar, except for the infrequent abnormal bleeding (Type I 15% versus Type II 4%, P  = 0.01). More women with Type I disease (57% versus 41%, P  = 0.04) had been referred for suspected gynaecological cancer. Median time from referral to diagnosis was 1.4 months for women with iEOC referred via a 2‐week cancer referral to any specialty compared with 2.6 months (interquartile range 2.0–3.7) for women who were referred routinely to gynaecology. Conclusion: Overall, shorter diagnostic delays were seen when a cancer was suspected, even if the primary tumour site was not recognised to be ovarian. Despite differences in carcinogenesis and stage for Type I and Type II iEOC, time to diagnosis and symptoms were similar. Referral patterns were different, implying subtle symptom differences. If symptom‐based interventions are to impact on ovarian cancer survival, it is likely to be through reduced volume rather than stage‐shift. Further research on histological subtypes is needed. Tweetable abstract: No difference in time to diagnosis for Type I versus Type II invasive epithelial ovarian cancers. Tweetable abstract: No difference in time to diagnosis for Type I versus Type II invasive epithelial ovarian cancers.